Knowledge, attitude and practice of tomato retailers towards hygiene and food safety in Harar and Dire Dawa, Ethiopia - Gemeda, Biruk A.; Amenu, Kebede; Girma, S.; Grace, Delia; Srinivasan, R.; Roothaert, R.; Knight-Jones, Theodore J.D. (Elsevier, 2023)
In this study, we assessed knowledge, attitude, and practices (KAP) related to tomato hygiene and food safety, among tomato vendors in the Ethiopian cities of Harar and Dire Dawa. From a total of 1498 tomato retail market vendors identified in the two cities through vendor mapping exercises, 151 outlets were randomly selected for a cross-sectional KAP survey on tomato handling, marketing, loss due to damage, safety, and hygienic practice. Tomato vendors claimed that they knew about food safety and hygiene, and risks associated with raw tomatoes. We found considerable variation in food safety knowledge, barriers, and practices during handling and marketing. The major concern of tomato traders in terms of food safety for vegetables was contamination with dirt. Around 17% of street vendors did not know about the importance of water quality and cleanliness for food safety. About 20% of tomato traders washed tomatoes after they purchased them and 43% and 14% of respondents who practiced tomato washing revealed that they cannot get the quantity and quality of water needed, respectively. Tomatoes were displayed in direct sunlight in about 85% of stalls. About 37% of vendors said rodents were present at night and could contact surfaces tomatoes are displayed on. For about 40% of outlets one or more flies were seen to be present on a third to two-thirds of their tomatoes. Overall, 40% of respondents reported they do not have adequate toilet facilities and 20% of those that use a toilet do not have water for washing hands after. The study identified areas that should be targeted by interventions aiming to improve food safety in this setting, however, without improvements in basic infrastructure to provide the pre-requisites for food safety the impact of small-scale food safety interventions may be limited.